Poverty Dynamics in Nepal between 2004 and 2011: An Analysis of Hybrid Dataset - Adhikari, Shiva Raj (NRB Economic Review, 2016)
Poverty trends describe changes in poverty incidence over time; however, this can mask poverty dynamics. Poverty dynamics discusses the length of time experiencing poverty and explains about movements into and out of poverty. Evidence on poverty dynamics is important for policy makers to design appropriate anti-poverty policies. Panel data is central to obtaining a better understanding of poverty dynamics. Due to the absence of panel data, the paper constructs hybrid dataset using two rounds of cross sectional surveys in 2003/04 and 2010/11 in Nepal to assess the poverty dynamics. Incidence of poverty estimated from hybrid dataset may not be directly comparable with the estimation of poverty through conventional approach. The results indicate that chronic poverty is almost 21 percent for 2003/04 and 2010/11. Movements into and out of poverty, non- poor to poor and poor to non-poor, are 6 percent and 14 percent respectively. Almost 60 percent people are in non-poor category in both periods. Chronic poverty exists in all regions, marginalized ethnic and Dalit (occupational caste) groups. Different anti-poverty policies are required to address chronic or transitory poverty. The policies or opportunities such as increasing credit facilities, increasing access to services, remittances, or social safety net programmes that can stabilize short-term income fluctuations may be more appropriate to address transitory poverty. In contrast, the policies that are related to structural or long-term interventions such as development of basic infrastructure, increasing of social and political inclusion, redistribution of assets, increasing rates of capital accumulation among others are required to address chronic poverty.